Technical Efficiency of Public Universities in Peru - Tello Miranda, Marco Antonio (2021)
Deficiencies in the quality of higher education are among Peru’s main weaknesses according to the world competitiveness ranking. Therefore, this study determined the technical efficiency (TE) of Peruvian public universities using data envelopment analysis (DEA). In addition, it analyzed the relationships between the experience and education quality of the institutions, and TE. The study covered the 42 public universities registered for 2016, which were measured in terms of one input and two outputs. It was concluded that Peruvian public universities have production functions of constant returns to scale (average OTE = 56.8 %), which served as a basis for classifying institutions into four categories according to their strategic orientations (high or low) towards research or universal education. It was also found that no relationship exists between TE and the experience or education quality of the institution.